Comparison of cataract patients with regular corneal astigmatism after implantation of extended range-of-vision and bifocal toric intraocular lenses - Li, Zhuoya; Guo, Rong; Hu, Xiaomin; Yang, Xinyue; Wen, Ziyuan; Lin, Yi; Zhang, Hui (Frontiers in Medicine, 2023)
Purpose To compare the postoperative visual acuity and visual quality between extended range-of-vision and multifocal toric intraocular lens (IOLs) after implantation in cataract patients with regular corneal astigmatism. Setting Department of Ophthalmology, the Second Hospital of Jilin University, Changchun, Jilin Province, China. Design Retrospective and single-center study. Methods The study involved implanting the Tecnis Symphony (ZXR00IOL) or the bifocal toric (ZMTIOL) in patients undergoing cataract surgery. Three months after surgery, lens performance was evaluated using distance, intermediate, and near visual acuity tests, defocus curves, the modulation transfer function (MTF), a visual function index questionnaire (VF-14), and the adverse optical interference phenomena. Results The 3-month postoperative follow-up found that both groups had good corrected distance vision. The ZMT group had better-uncorrected distance visual acuity and near visual acuity (p < 0.05). However, the ZXR group showed better uncorrected intermediate visual acuity (p < 0.05) and visual continuity. Overall astigmatism in the postoperative ZMT group was significantly lower than that in the pre-operative group (p < 0.05). The ZMT group had lower total high-order aberrations (tHOs), higher MTF values, and higher VF-14 scores (p < 0.05). Finally, the ZXR group exhibited reduced halo and glare phenomena (p < 0.05). Conclusion We found that ZMT can effectively correct a corneal astigmatism of 1.0–1.5 D and ZXR can improve patient outcomes regarding subjective optical quality and range of vision. These findings have the potential to improve future astigmatism treatment options.